(untitled) (European Journal of Marketing and Economics, 2024)
Customer complaints and dissatisfaction have worsened nowadays because of poor quality service delivery by organizations’ frontline sales personnel. However, the influence of customer-oriented salespersons’ selling approaches necessary for achieving customer satisfaction in the hospitality industry was investigated. The exact objectives were to determine the influence of consultative selling on customer satisfaction in the hospitality industry, to examine the influence of solution selling on customer satisfaction in the hospitality industry, and to explore the influence of relationship selling on customer satisfaction in the hospitality industry. The study comprises customers of selected fast-food restaurants in Enugu metropolis whose population is non-finite. Using Cochran’s formula, the sample size of 384 was obtained and subsequently, the survey method was adopted and copies of structured questionnaires were distributed to the 384 respondents who returned 300 properly filled copies of the questionnaire. Cronbach’s alpha was used in conducting the reliability test and 0.895 was obtained, indicating that there is internal consistency. Furthermore, analysis of data was done using simple linear regression and the findings revealed that consultative selling has a significant and positive influence on customer satisfaction in the hospitality industry. Similarly, it was revealed that solution selling has a significant and positive influence on customer satisfaction in the hospitality industry. Moreover, it was revealed that relationship selling has a significant and positive influence on customer satisfaction in the hospitality industry. Consequently, salesperson’s customer-oriented selling traits such as consultative selling, solution selling, and relationship selling have proven to trigger customer satisfaction, thus, managers are encouraged to recruit salespersons with customer-oriented characteristics to enhance revenue generation and profitability via improved customer acquisition, relationship, satisfaction, retention, and loyalty.